Identification of Potential Diagnostic Markers for Depressive Disorders using Urinary Biomarkers of N-Methylnicotinamide and Hippuric Acid - Susanto, Nadila Apriola; Hasanah, Uswatun; Sutrisno, AL-Bidarri Tsamira Annafila; Hani, Handini Risma; Asih, Sekar; Agustini, Sulistyo Mulyo (Jurnal Psikiatri Surabaya, 2024)
Introduction: The diagnostic methodology for depressive disorders, relying on symptom clusters, has inherent limitations in ensuring heterogeneity levels. Consequently, this presents a notable risk of inevitable diagnostic errors in mental health assessments. Therefore, advocating for objective diagnostic approaches through empirical testing in clinical settings becomes crucial for individuals dealing with depressive disorders. This study aims to identify the effectiveness of urine as a diagnostic support for depressive disorders using the N-Methylnicotinamide and Hippuric Acid biomarkers. Methods: This study used 13 urine samples from patients with depressive disorders and 13 normal urine samples. It used ELISA methods with observational analytic and cross-sectional designs. Results: The results showed that the N-methylnicotinamide biomarker had a relationship with depressive disorders with a correlation value of 0.867, while hippuric acid obtained a correlation value of 0.692. Besides, the N-Methylnicotinamide and Hippuric Acid biomarkers showed differences in the urine of depressive disorder and normal patients with significance values of 0.000 and 0.001 for the N-Methylnicotinamide and Hippuric Acid biomarkers, respectively. In addition, the Relative Operating Characteristics curve analysis showed that these two biomarkers had good sensitivity and specificity values in assisting the diagnosis of depressive disorders. N-methylnicotinamide has a sensitivity of 92.3% and a specificity of 100%, while hippuric acid has a sensitivity of 76.9% and a specificity of 84.6%. Conclusions: Significant differences in the biomarkers of N-methylnicotinamide and hippuric acid in the urine of depressed patients compared to normal patients. Therefore, these biomarkers can be the empirical laboratory methods to support the diagnosis of depressive.